Analisis Bimbingan dan Konseling dalam Lingkup Pendidikan - Nurul Hafizhah Salsabila Sitorus; Tarisha Putri; Mhd. Haical Eriyanto; Silvy Nurhasanah; Rosita Dongoran (Journal on Education, 2024)
Guidance and counseling are interpersonal activities between counselors and counselees that aim to guide, assist, or direct counselees in solving the problems they face and living life well in general. Guidance and counseling in education is a serious effort to develop the character, abilities, interests, and talents of students. The purpose of this study is to describe and elaborate the essence of guidance and counseling in the scope of education. This research uses a qualitative method with a literature study approach and is descriptive analysis. Data collection uses literature study. The results showed that guidance and counseling have an important essence in education. Counseling guidance and education have the same vision and mission, which is to help students in living life in educational institutions properly and optimally. The importance of guidance and counseling in education is to ensure that students receive the right support to achieve their maximum potential, overcome problems that arise, prepare for the future, and achieve well-being. Therefore, the implementation between counseling and education has a balance and attachment to each other.